FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LABA BERDASARKAN ASPEK GOOD CORPORATE GOVERNANCE - Hari Prasetyo Kusuma Dharma, (2022)
This study is a quantitative research that aims to examine the effect of managerial ownership, institutional ownership, and independent audit committee on the earnings quality with firm size as a control variable. This study uses secondary data from annual reports of manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange for period 2018-2020. Total sample used for this study is 57 samples using panel data regression as an analytical method with tools by Eviews 10. The result of this study prove that managerial ownership, institutional ownership and independent audit committees have no effect on earnings quality.